On the End of a Nightmare (COVID-19). The Role of the Immune System - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2022)
After the Chinese epidemic of Wuhan and the global pandemic that followed, the spread of the coronavirus CoV-SARS-2 has finally come to an end. Already declared the end in the United Kingdom on 19 July 2021, which had primarily started vaccinations on 8 December 2020, aimed in particular at "over" 80 and frail subjects, the whole world has aligned, in particular also taking into account the therapies oral and monoclonal antibodies with a virus that while maintaining its contagiousness has reduced in its virulence. The African continent has stood out for its endemicity linked to zoonoses of the beta coronavirus family. Finally, particular importance is given to the natural infection from COVID-19 and to the immune response with the vaccination exemption due to the risk of thrombi due to genetic mutation and antibody overload.